Variabilitas Temperatur Permukaan Laut, Salinitas, dan, Curah Hujan Pada Periode El Niño-Southern Oscillation (Enso) di Perairan Selat Madura - Jennifer Ellen Toding; Supriyatno Widagdo; Rudi Siap Bintoro (Universitas Hang Tuah, 2022)
The variability of temperature, salinity and rainfall in the Indonesian region is strongly influenced by the El Niño-Southern Oscillation (ENSO) phenomenon so that this study aims to describe the characteristics of the ENSO phenomenon, compare and analyze the characteristics of temperature, salinity and rainfall under normal conditions and changes due to the ENSO phenomenon in the Madura Strait. This study used a descriptive method by collecting data using secondary data and making a description of the observed phenomenon. Data required for 12 years from 2010-2021. The results showed that the variability of temperature measured during the 2010-2021 period showed the highest temperature values were in the closed waters of the Madura Strait with an average of 28.64°C and the lowest were in the central waters with an average value of 28.59°C. The highest rainfall value is in closed waters with an average of 6.06 mm and the lowest is in central waters with an average value of 5.562 mm. The highest salinity is in open water with an average value of 32.06 ppt while the lowest salinity is in closed water with an average of 31.42 ppt. The highest temperature and rainfall are generally found when the La Niña phenomenon is taking place, while the lowestntemperature and rainfall are found during the El Niño phenomenon. The highest salinity is generally found during the El Niño phenomenon, while the lowest salinity occurs during the La Niña phenomenon.